Inter-industry wage differentials in EU countries: What do cross-country time varying data add to the picture? - Philip Du Caju; Gábor Kátay; Ana Lamo; Daphne Nicolitsas; Steven Poelhekke (Magyar Nemzeti Bank, 2010)
This paper documents the existence and main patterns of inter-industry wage differentials across a large number of industries for 8 EU countries (Belgium, Germany, Greece, Hungary, Ireland, Italy, Netherlands, and Spain) at two points in time (in general 1995 and 2002) and explores possible explanations for these patterns. The analysis uses the European Structure of Earnings Survey (SES), an internationally harmonised matched employer-employee dataset, to estimate inter-industry wage differentials conditional on a rich set of employee, employer and job characteristics. After investigating the possibility that unobservable employee characteristics lie behind the conditional wage differentials, a hypothesis which cannot be accepted, the paper investigates the role of institutional, industry structure and industry performance characteristics in explaining interindustry wage differentials. The results suggest that inter-industry wage differentials are consistent with rent sharing mechanisms and that rent sharing is more likely in industries with firm-level collective agreements and with higher collective agreement coverage.
Keywords: J31; J41; J51; 330; inter-industry wage differentials; rent sharing; unobserved ability; Sektorale Lohnstruktur; Humankapital; Unternehmenserfolg; Lohnbildung; Erfolgsbeteiligung; EU-Staaten